(untitled) (Global Business Management Review (GBMR), 2022)
Small and medium scale enterprises (SMEs) are one of the fastest growing and most dynamic sectors in every economy. The industry is highly labour intensive and for that reason effective recruitment is significant for success. However, the issue of best recruitment practice (BRP) in SMEs has been neglected by researchers and practitioners. This study aimed to address this gap by examining the best recruitment practice and the effect on the achievement of high performance organizations (HPO) in SMEs. The analysis was based on a survey of 354 senior managers that had spent ten years and above in SMEs in the Nigerian market. The result showed that BRP had a significant positive impact on the achievement of HPO. This paper provides an insight into the applicability of BRP as well as offers practical help to human resource practitioners embarking on the best recruitment practice in the achievement of HPO. Managers and human resource professionals can use the result of this study to weigh the adaptability of BRP within the context of SMEs in developing economies.